Photo-Induced Selective Difluoroalkylation of Unactivated Alkenes to Access Difluoroalkylated Indoles - Tong, Jinghui; Luo, Renshi; Liu, Liang; Yang, Xiao; Liao, Jianhua (Synthesis, 2023)
The difluoroalkylation of unactivated alkenes with ethyl iododifluoroacetate via visible light-induced process has been developed. This transformation provides selective access to difluoroalkylated indole derivatives in good yields depending on the choice of base, solvent, as well as the loading of ethyl iododifluoroacetate.
Keywords: alkenes; cycloaddition; indoles; radical reaction; photooxidation